Changes in mental health, pain, and drug misuse since the mid-1990s: Is there a link?. (February 2020) - Glei, Dana A.; Stokes, Andrew; Weinstein, Maxine
Abstract: Drug-related mortality in the US grew dramatically in recent years, while mental health deteriorated among disadvantaged Americans and reported levels of pain increased over the same period. Here we investigate whether increased prevalence of drug misuse between the mid-1990s and early-2010s is associated with higher levels of mental distress and pain. Our results demonstrate higher drug misuse over this period, particularly for older and for socioeconomically disadvantaged Americans. After adjusting for sociodemographic characteristics, we estimate that the prevalence of drug misuse increased by 19 percentage points among those aged 50–76 in the bottom percentile of socioeconomic status (SES). Misuse increased much more at older than at younger ages for all drug types except sedatives, which increased to a similar degree in both age groups. Compared with measures of mental health, pain consistently accounted for a greater share of the period differential in drug misuse among both age groups and across all drug types. Misuse of prescription painkillers exhibited the largest difference in the contributions of pain versus mental health: among older individuals with the lowest SES, pain explained three times as much of the period trend as mental health (60% vs. 19%). Pain was more closely linked with the rise in misuse of prescription painkillers than other drugs. Mental health is a strong correlate of drug misuse (particularly sedative use), but growing drug misuse since the mid-1990s was more strongly linked with rising levels of reported pain than with deterioration in mental health. Pain could be a key factor underlying the association between trends in mental health and drug use: higher levels of pain may contribute to both mental distress and drug misuse. Given that pain, mental distress, and drug misuse are intertwined, successful intervention may require addressing all three factors. Highlights: Drug misuse increased since 1995–96 for those with lower socioeconomic status. Except for sedatives, misuse increased more at older than at younger ages. Mental health accounted for only a small part of the increase in misuse. Pain explained most of the period trend in misuse of prescription painkillers. Pain contributed more than mental health to the rise in misuse of all drug types.